Religious Moderation Communication in Peace Diplomacy: Analysis of Prabowo Subianto’s Speech at the 2025 UN General Assembly - Huri, Vivi Silvia; Fikri, Muhammad Rozan; Satriah, Lilis; Rosyidi, Imron (LifeSciFi, 2026)
This study is motivated by the growing importance of moderate religious communication as a diplomatic strategy to address rising global conflicts, particularly the Israel–Palestine issue. It aims to analyze how moderate religious communication was employed by President Prabowo Subianto in his speech at the 2025 United Nations General Assembly as an instrument of Indonesia’s diplomacy in supporting peaceful solutions. The research applies a qualitative approach using diplomatic discourse analysis, examining the verbal messages, symbolic expressions, and humanitarian values conveyed in the speech. The findings show that Prabowo applied a moderate communication strategy using simple and peaceful language, interfaith greetings, and an emphasis on universal humanitarian values that position all humankind as one global family. The main results highlight that religious moderation serves as a foundation of Indonesia’s diplomacy, reflected in the rejection of extremism, support for the two-state solution, and calls to build global solidarity based on justice and human dignity. This approach strengthens Indonesia’s position as a credible mediator in the Palestine issue by promoting tolerance, interfaith dialogue, and non-violent values. The study implies that moderate religious communication can serve as an effective diplomatic model for multicultural countries in reducing international conflict, building global trust, and reinforcing Indonesia’s soft power in the modern geopolitical landscape.